2019
DOI: 10.1111/mpp.12865
|View full text |Cite
|
Sign up to set email alerts
|

Stringent response regulators (p)ppGpp and DksA positively regulate virulence and host adaptation of Xanthomonas citri

Abstract: SummaryThe bacterial stringent response is a response to nutrition deprivation and other stress conditions. In Gram‐negative bacteria, this process is mediated by the small signal molecules guanosine pentaphosphate pppGpp and guanosine tetraphosphate ppGpp (collectively referred to as (p)ppGpp), and the RNA polymerase‐binding transcription factor DksA. The (p)ppGpp synthetase RelA and the bifunctional (p)ppGpp synthase/hydrolase SpoT are responsible for cellular (p)ppGpp levels. Here, we investigated the roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 91 publications
1
23
0
Order By: Relevance
“…Stringent response in bacteria is induced by stress or metabolite starvation [ 73 ] and is mediated by internal levels of guanosine pentaphosphate [(p)ppGpp], which is synthesized and degraded by RelA and SpoT [ 73 ]. It was recently reported that deletion of relA and spoT homologs in Xcci completely abolished pathogenicity in citrus and caused a significant reduction in the expression of hrpG, hrpX, and their downstream targets [ 74 ]. Similar phenotypes were observed upon deletion of transcriptional regulator dksA [ 74 ], which is associated with alteration of the affinity of the RNA polymerase to (p)ppGpp [ 75 ] ( Figure 2 ).…”
Section: Metabolic Regulation Of the Hrpg/hrpx Regulonmentioning
confidence: 99%
See 2 more Smart Citations
“…Stringent response in bacteria is induced by stress or metabolite starvation [ 73 ] and is mediated by internal levels of guanosine pentaphosphate [(p)ppGpp], which is synthesized and degraded by RelA and SpoT [ 73 ]. It was recently reported that deletion of relA and spoT homologs in Xcci completely abolished pathogenicity in citrus and caused a significant reduction in the expression of hrpG, hrpX, and their downstream targets [ 74 ]. Similar phenotypes were observed upon deletion of transcriptional regulator dksA [ 74 ], which is associated with alteration of the affinity of the RNA polymerase to (p)ppGpp [ 75 ] ( Figure 2 ).…”
Section: Metabolic Regulation Of the Hrpg/hrpx Regulonmentioning
confidence: 99%
“…It was recently reported that deletion of relA and spoT homologs in Xcci completely abolished pathogenicity in citrus and caused a significant reduction in the expression of hrpG, hrpX, and their downstream targets [ 74 ]. Similar phenotypes were observed upon deletion of transcriptional regulator dksA [ 74 ], which is associated with alteration of the affinity of the RNA polymerase to (p)ppGpp [ 75 ] ( Figure 2 ). These observations suggest that hrp gene expression is regulated by internal levels of (p)ppGpp that are presumably controlled by nutrient limitation.…”
Section: Metabolic Regulation Of the Hrpg/hrpx Regulonmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell cultures were distributed in the wells of a 24-wells microtiter plate and incubated in a microtiter plate reader (Synergy H1M1; BioTek) at 30˚C with constant agitation (200 rpm) and OD 600 nm were measured every 30 min for 20 hours [24]. The in planta growth curves were performed according to procedures outlined by Zhang et al [25], with modifications. The bacterial cultures were adjusted to 10 6 CFU/mL with sterile 10 mM MgCl 2 solution and infiltrated into the abaxial surface leaves of Valencia sweet orange (Citrus sinensis) using a needleless syringe.…”
Section: Growth Curves and Pathogenicity Assaysmentioning
confidence: 99%
“…However, under iron limiting conditions (for example, in vivo ), Fur cannot bind the sequence of the Fur box resulting in derepression of genes that encode siderophore transporters (including TBDTs), proteins involved in siderophore biosynthesis and iron metabolism ( Figure 2 ) ( Lee and Helmann, 2007 ; Noinaj et al., 2010 ). In addition to Fur, multiple regulatory factors including small RNAs, ChvR ( Frohlich et al., 2018 ), OmrA and OmrB ( Guillier and Gottesman, 2008 ), string response regulators (P) ppGpp and DksA ( Zhang et al., 2019 ), participate in the regulation of TBDTs for siderophore.…”
Section: Characteristics Of Tbdts Make Them Excellent Candidates For mentioning
confidence: 99%